Peculiarities of procedural decision-making during pre-trial investigation of high-profile offences a sexual nature committed against children - T. H. Fomina; O. V. Pchelina (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of regulatory legal acts and investigative and judicial practice, certain peculiarities of procedural decision-making during pre-trial investigation of high-profile criminal offences of a sexual nature committed against children have been highlighted, namely, with regard to: the formation of an investigative team or an investigative and operational team; the application of security measures; the conduct of criminal proceedings in a closed court session; and the application of measures to ensure criminal proceedings.